Answer:
[tex]F=-2A[\frac{1}{x^3}\hat{i}+\frac{1}{y^3}\hat{j}][/tex]
Explanation:
You have the following potential energy function:
[tex]U(x,y)=A[\frac{1}{x^2}+\frac{1}{y^2}}][/tex] (1)
A > 0 constant
In order to find the force in terms of the unit vectors, you use the gradient of the potential function:
[tex]\vec{F}=\bigtriangledown U(x,y)=\frac{\partial}{\partial x}U\hat{i}+\frac{\partial}{\partial y}U\hat{j}[/tex] (2)
Then, you replace the expression (1) into the expression (2) and calculate the partial derivatives:
[tex]\vec{F}=A\frac{\partial}{\partial x}[\frac{1}{x^2}+\frac{1}{y^2}]} \hat{i}+A\frac{\partial}{\partial x}[\frac{1}{x^2}+\frac{1}{y^2}]\hat{j}\\\\\vec{F}=A(-2x^{-3})\hat{i}+A(-2y^{-3})\hat{j}\\\\F=-2A[\frac{1}{x^3}\hat{i}+\frac{1}{y^3}\hat{j}][/tex](3)
The result obtained in (3) is the force expressed in terms of the unit vectors, for the potential energy function U(x,y).